Arsitektur Enterprise Sistem Informasi Institusi Perguruan Tinggi Menggunakan Zachman Framework - Dwi Agustina Martuti; Teguh Susyanto; Setiyowati Setiyowati (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2020)
The higher education program in Indonesia is developing and growing very rapidly and which is followed by the increasing business needs of the organization. Increasing the data and information in business functions which is conducting by college became the use of information systems the college. The lack of planning in appropriate developing information system process will obstruct on completing university’s strategies. In this study, the method of collecting data and information is observing and interviewing system users and collecting documents related to business processes. The design of enterprise architecture uses the Zachman Framework with the perspective of the planner (scope), owner (business model), and designer (system model). The researchers expect that the result can be a roadmap for the planning design which is proposed to make it easier for students and employees.Keywords: Blueprint, Strategic Planning, Enterprise Architecture, Zachman Framework